Comparison of interatomic potentials on crack propagation properties in bcc iron. (1st December 2021) - Ji, Hua; Wang, Yi; Yin, Jian; Hou, Huaiyu; Lai, Wensheng; Mei, Jinna; Xue, Fei; Liu, Baixin; Liu, Jianbo
Abstract: Atomistic simulations with interatomic potentials can provide insights into the cracking and failure of structural ferritic steels. Unfortunately, the evaluation of the simulation results often suffers from the uncertainties due to the quality and behavior of the employed interatomic potential. In this work, the molecular dynamics (MD) method has been used to simulate and to analyze the deformation and propagation of crack tips in α- iron. The influence of different types of potentials that we adopt on the crack propagation simulation is discussed. State of art M07, M20, and B20 potentials are considered. Overall, the microscopic deformation mechanism by the MD simulation with different types of potentials are similar, which dislocations are emitted from the crack tip, and twinning or martensite transformation happen. However, with a careful contradistinction, different mechanical responses are investigated. The relationship between the cracking mechanism and the intrinsic properties of α- iron, such as stacking fault energies, has also been discussed. Highlights: The influence of M07, M20, and B20 potentials on the crack propagation MD simulation in α-iron is discussed. The calculated GSFE curves of M07, M20, and B20 potentials are compared with the DFT results from the literatures. The deformation process of the crack propagation in α-iron is revealed better described by the M20 potential.